2016
DOI: 10.1002/tcr.201600035
|View full text |Cite
|
Sign up to set email alerts
|

When Inert Becomes Active: A Fascinating Route for Catalyst Design

Abstract: Abstract:In this personal account, we review the work of our group in the area of energy and environment related nanocatalysis in the past seven years. We focus on understanding the fundamental mechanisms, which control properties of atomic clusters and nanoparticles -a form of matter that is intermediate between atoms and their bulk counterpart. The emphasis is made on the theoretical design of effective catalysts based on cheap and abundant elements. The main idea that stands behind of our work is that even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 62 publications
(67 reference statements)
2
27
0
Order By: Relevance
“…Therefore until recently such material has never been considered as a possible candidate for electrocatalyst. However in our previous works we have demonstrated theoretically that h-BN is not as inert as it was previously believed and can strongly affect the catalytic properties of the supported metal particles [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Therefore until recently such material has never been considered as a possible candidate for electrocatalyst. However in our previous works we have demonstrated theoretically that h-BN is not as inert as it was previously believed and can strongly affect the catalytic properties of the supported metal particles [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 83%
“…It is important to note that adsorption energies of intermediates of catalytic reactions can be strongly affected by the density of electronic states (DOS) near the Fermi level. Therefore, a metal substrate or defects in h-BN can promote or affect catalytic reactions on the h-BN surface [38]. This theoretical suggestion has been proved experimentally where it has been demonstrated that Au electrodes modified with boron nitride nanosheet (BNNS) in the acid media indeed can act as effective electrocatalysts not only for ORR [47,48], but also for the hydrogen evolution reaction (HER) [49].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…By virtue of an exceptional chemical and thermal stability, large surface area, high thermal conductivity, and strong surface adsorbing capability, two-dimensional (2D) hexagonal BN nanosheets (h-BN or BN in this paper), a structural analog of graphene, are one of the most attractive transition metal catalysts supports (28)(29)(30). The pristine BN surface is an inert support for metal nanoclusters, which would lead to catalyst deactivation by sintered metal species (31,32). Thanks to the chemical modification/doping or defect engineering, BN owns greater possibilities in changing physical and chemical characteristics for catalysis development.…”
Section: Significancementioning
confidence: 99%